Fabrication and Characterization of Hydroxyapatite Bead for Water Filter Application - Abdullah, Hasan Zuhudi; Albi, Norazlinda (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Hydroxyapatite and related calcium phosphate compounds have similarities in composition with natural bone. From a chemical and structural point of view, HAp with the stoichiometric formula (Ca10(PO4)6(OH)2) and a Ca/P molar ratio is 1.67. Natural HAp is obtained from animal bones such as pig, bovine, cuttlefish and fish with preserve some properties of the precursor material such as chemical composition and structure. HAp has been used in bone grafts, dental implant coatings, toothpaste and water filter applications. Hydroxyapatite can adsorb bacteria and viruses effectively, hence it can be used as a filter to filtrate the bacteria and viruses in the air or liquid. The aim of this study was to produce hydroxyapatite (HAp) beads from the fish scale for water filter applications and to obtain hydroxyapatite (HAp) from waste fish for producing ion calcium in the water. The morphology and physical properties of hydroxyapatite (HAp) beads were investigated in this study. The calcined HAp powder and HAP beads were characterized by Fourier Transform Infrared Spectroscopy (FTIR) to analyse the chemical bonding, elemental analysis by using Energy Dispersive X-Ray (EDX) and Field Effect Scanning Electron Microscope (FESEM) to analyze the microstructure. The calcination of Tilapia fish bone to derive HAp was evaluated at different temperatures, namely 700 ̊C and 800 ̊C. The HAp beads were sintered at two different temperatures of 1000 ̊C and 1250 ̊C for 3 hours. FTIR results revealed the presence of carbonate and hydroxyl groups at low calcination temperature and disappear when the temperature rises. From the FESEM result, the crystallinity increases when the temperature increases. In terms of correlation with water, high sintering temperature produces high calcium concentrations. It can be concluded that HAp can be produced from natural sources.